أثر المشاركة في سلاسل القيمة العالمية على الدول العربية - باهي, عبد المالك; باهي, وفاء; جديدي, هالة (University of eloued جامعة الوادي, 2017)
This thesis attempted to measure the impact of the participation of eight Arab countries in global value chains as an input to integration into, and promotion of the global economic system through a standard model that tests the impact of growth of: domestic and foreign added value in total exports, foreign direct investment, trade openness, effective real exchange rate, and finally the growth of exports of goods and services, On the indicators of human development and unemployment, GDP per capita growth, BoP, and growth of investment. The standard models were evaluated using Eviews9.5 and Stata14 using the pooled mean group PMG methodology, the Panel unit root tests were performed for the panel data to determine the level of stability of the study’s variables. In order to verify the existence of a cointegration between the dependent variable and its determinants, we have carried out Kao cointegration test in which we have been able to prove the existence of a long-term relationship between the dependent and independent variables studied. The results of the study revealed a significant relationship between dependent variables and most of their independent variables.
مذكرة ماستر تجارة دولية
Keywords: اقتصاديات الدول العربية، سلاسل القيمة العالمية، المنظومة الاقتصادية العالمية،التنمية الاقتصادية; Economies of Arab Countries (Eight Countries), Global Value Chains, World Economic System, Economic Development, Standard Modeling (PMG).